History, Hermeneutics and the Unity of Luke-Acts - Rowe, C. Kavin (Journal for the study of the New Testament, 2005)
This article attempts to raise questions on the basis of the early reception history of Luke and Acts about the relation between a literary-critical interpretation and an interpretation of Luke's work that asks after its meaning for an early Christian audience. That Luke-Acts can be read as a literary unity is not challenged. But the evidence that we have suggests that Luke and Acts were not read/heard together by the early Christians in the ancient world. We may thus ask whether our interpretations that depend in principle on the unity of Luke-Acts are in fact not as historical as we might suppose, at least in the sense that the texts would not have been heard together in the way we read them today. Conversely, we may also ask whether a historical interpretation that seeks to read Luke and Acts as they were most likely heard is of necessity estranged from the literary dynamics of Luke-Acts.